SHARIA PHILOSOPHY OF ISLAMIC LAW - Andi Fadhil Andi Aderus; Achmad Musyahid; Rahmatiah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Islamic law has unique characteristics as a guideline for regulating the life of a servant. By knowing the principles of the wisdom contained in the character of Islamic law, the practice in applying Islamic law can run optimally and be able to follow the guidance of Allah swt as a figure who lowers the sharia. The principles of convenience, divinity, benefit, and balance between physical and spiritual are the main keys to the value of Islamic law itself.